Application of metagenomic next-generation sequencing in the diagnosis and treatment of acute pneumonia caused by Tropheryma whipplei - Yinping Huo; Chao Wu; Dawen Ma (BMC Pulmonary Medicine)
Abstract Objective The treatment plan and process for acute pneumonia caused by Tropheryma whipplei have not been clearly defined. The study aimed to conduct a retrospective analysis of the treatment for patients with acute pneumonia, caused by Tropheryma whipplei, diagnosed through metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF). Methods All patients underwent routine blood examinations and chest CT scans. Electronic fiberoptic bronchoscopy was performed to collect BALF samples from the lesion subsegments. The BALF samples were subjected to mNGS analysis. During hospitalization, all patients were treated with imipenem-cilastatin combined with compound sulfamethoxazole (SMZ-TMP) tablets for anti-infection, and they took SMZ-TMP orally for 3 months after discharge and followed up. Results We identified 7 cases where Tropheryma whipplei was the primary pathogen, with 3 of these cases having it as the sole detected pathogen. The clinical manifestations of acute Tropheryma whipplei pneumonia are atypical. Chest CT scans revealed that 3 cases had exudative lesions in both lungs, 4 cases had unilateral pulmonary exudative lesions, 3 cases had bilateral pulmonary nodules, 2 cases had interstitial changes, and 3 cases had pleural effusion. Following treatment, all follow-up cases showed no recurrence. Conclusions The mNGS examination of bronchoalveolar lavage fluid can significantly improve the early diagnosis of acute pneumonia caused by Tropheryma whipplei. The treatment involving imipenem-cilastatin combined with SMZ-TMP, followed by oral SMZ-TMP for three months, is effective.